Implementation of Different Types of Photovoltaics on Greenhouses: A Case Study - Angela Najdoska and Goga Cvetkovski (Faculty of Electrical Engineering and Information Technologies, Ss. Cyril and Methodius University in Skopje, North Macedonia, 2022)
In the past few years, during the global pandemic and now the energy and economic crisis, the demand for electrical energy is constantly rising. Consequently, the implementation of photovoltaic power plants on a big scale is rising. Most of the time, these photovoltaic power plants are installed on the ground, and in most of the cases it is a fertile soil, meaning we are using the land for making electrical energy. This study aims to presents a case study in which the photovoltaics are implemented on greenhouses in order to be energy neural. Also, to produce electrical energy, so that the land is used for growing plants and producing electrical energy .
Keywords: Photovoltaic systems, Solar energy, Agrovoltaics